2011
DOI: 10.1016/j.juro.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Voiding Cystourethrogram—Are Our Protocols the Same?

Abstract: Data reveal that voiding cystourethrogram is performed differently across North America and no standard protocol exists for the procedure. These differences could significantly impact voiding cystourethrogram results among institutions and taint our ability to compare results in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Recent studies have demonstrated significant variability among institutions with no standardized VCUG protocols, as well as lack of consistent reporting practices. 25,26 In addition to potential child and parental distress, VCUGs also expose the patient to radiation, albeit at low doses. 27 While benefits generally outweigh the risks, it is logical to maximize the quality of data obtained from a single VCUG by collaboration with our radiology colleagues to generate complete reports.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Recent studies have demonstrated significant variability among institutions with no standardized VCUG protocols, as well as lack of consistent reporting practices. 25,26 In addition to potential child and parental distress, VCUGs also expose the patient to radiation, albeit at low doses. 27 While benefits generally outweigh the risks, it is logical to maximize the quality of data obtained from a single VCUG by collaboration with our radiology colleagues to generate complete reports.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Across North America, most VCUG protocols are identical: parents’ presence, contrast infusion by gravity, thin catheter without balloons, no contrast dilution and voiding without a catheter in place. Differences among institutions were the height of contrast medium and when to stop filling contrast medium . However, no significant differences in the VUR detection rate between two different heights of 50 cm or 100 cm were reported .…”
Section: Practical Guide For Carrying Out Vcugmentioning
confidence: 92%
“…Voiding cystourethrography has unique ability to provide detailed information about both the anatomical and functional status of the urinary tract. However, the literature has shown significant variability among institutions regarding the VCUG protocol used, as well as inconsistent reporting of the findings from the VCUG between institutions . Although VUR grade is routinely reported, other crucial anatomical and functional findings are consistently underreported.…”
Section: How To Perform a Vcugmentioning
confidence: 99%